A wheat germ-rich diet preserves bone homeostasis by regulating gut microbiota and plasma metabolites in aged rats - Luanfeng Wang; Zebin Weng; Tong Chen; Yu Li; Ling Xiong; Haizhao Song; Fang Wang; Xiaozhi Tang; Bo Ren; Xuebo Liu; Xinchun Shen (Food Science and Human Wellness)
Bone loss caused by ageing has become one of the leading health risk factors worldwide. Wheat germ (WG) is consists of high amounts of bioactive peptides, polyunsaturated fatty acids, and dietary fibre. Currently, WG has been proven to possess strong antioxidant and anti-inflammatory properties. We recently explored the beneficial effects and relevant mechanisms of a WG-rich diet (2.5% and 5% WG, m/m) on bone homeostasis in aged rats. Our results showed that 5% WG supplementation for 12 months effectively attenuated ageing-induced microstructural damage and differentiation activity changes in the femur. The 5% WG supplementation also significantly increased the levels of total antioxidant capacity (T-AOC), glutathione peroxidase (GSH-Px) (P < 0.01), and superoxide dismutase (SOD) (P < 0.05), and decreased inflammatory cytokine levels (tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6)) (P < 0.01). Furthermore, the WG-rich diet reshaped the composition of the gut microbiota, enhancing short-chain fatty acids (SCFAs)-producing microbes and reducing inflammation-related microbes. In addition, metabolomics analysis showed that 5% WG supplementation improved plasma metabolites related to bone metabolism. Conclusively, our study purports long-term WG-rich diet may preserve bone homeostasis by regulating gut microbiota and plasma metabolites in aged rats.